2022
DOI: 10.3390/su14031766
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Drones for Last-Mile Delivery: A Numerical Case Study in Milan, Italy

Abstract: The increasing use of e-commerce introduces major challenges for last-mile delivery, which is critical to ensure smooth functioning of supply chains. Besides the speed and cost of delivery, which are the most important factors for last-mile logistics, environmental and social sustainability factors are taking on an increasingly important role, especially in urban areas. In this perspective, last-mile delivery by drones could be a good choice both in terms of transport speed and sustainability. Being electrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 39 publications
2
22
1
2
Order By: Relevance
“…SP surveys are most widely used in transportation studies to reveal how changes to infrastructure or services will alter travel shift behaviour. These are SP survey questionnaires that desire to gather data on the stated behaviour of mode users towards hypothetical stated contexts [ 19 ]. An SP questionnaire was prepared to understand commuter shift behaviour.…”
Section: Modelling Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…SP surveys are most widely used in transportation studies to reveal how changes to infrastructure or services will alter travel shift behaviour. These are SP survey questionnaires that desire to gather data on the stated behaviour of mode users towards hypothetical stated contexts [ 19 ]. An SP questionnaire was prepared to understand commuter shift behaviour.…”
Section: Modelling Approachmentioning
confidence: 99%
“…It is true from the model output that suburban rail passengers falling in the age group of 21-40 (+0.317/ t stat: +2.14), with monthly income 15,001-20,000 (+0.413/ t stat: +2.34) are more willing to use metro, while daily travellers are reluctant to use metro (−0.744/ t stat: −3.94). (2) From the correlation value, it is observed that the suburban travellers with age greater than 60 fall in the income range of INR 10,000-15,000 (r = +0 19…”
mentioning
confidence: 99%
“…In Table 3, we vary five different parameters, which are the number of stores M, varying from one of these possible values: {10, 15, 20, 25, 30}; and the number of products N, varying from one of these possible values: {100, 120, 140, 160, 180, 200}. We set the cardinality constraints c i , i ∈ M of the online stores from the uniform distribution whose ranges are from { [4,6], [6,8], [8,10], [10,12], [12,14], [14,16]}; customers' no-purchase preference on product u 0 i vary from these values: {10, 20, 30, 40, 50}; and purchase preference u j ik vary from the uniform distribution whose ranges are from {[0, 1], [1, 2], [2,3], [3,4], [4,5]}. Therefore, we have a total of 27 scenarios.…”
Section: Effectiveness Of Milp and Conic + MCmentioning
confidence: 99%
“…Other factors are gender, age, and household income, which reflects that the younger the age, the higher the preference for drone delivery service. Borghetti et al designed a goods delivery service by drone based on a preference survey [4]. The result showed that last-mile delivery by drones is appropriate for small and light packages.…”
Section: Introductionmentioning
confidence: 99%
“…These are SP survey questionnaires that aim to collect data on the stated behaviour of users towards hypothetical available contexts (Borghetti et al, 2022).…”
Section: Revealed Preference Approachmentioning
confidence: 99%